Efficacy of bacteria and caffeine as indicators of anthropogenic waste in freshwater systems - Fligg, Nathan (My University, 2018)
With urban sprawl and intensified agriculture, nutrient loading of waterways has become a pressing issue across southern Ontario. Domestic wastes are more likely than other wastewater sources to be associated with the presence of human pathogens, and therefore they may present a greater public health risk in watersheds. Field studies were performed in the watersheds of the County of Simcoe, ON to assess the efficacy of tracing nutrient loads directly attributable to domestic waste using caffeine as an indicator, and comparing caffeine patterns with those seen with conventional bacterial assessments such as heterotrophic plate count, total coliforms, fecal coliforms, and E.coli counts. Seasonal fluctuations in the levels of caffeine in these systems, both in water and surface sediments, were also studied. In a controlled experiment in the laboratory, a one-week study investigated the efficacy of standard bacterial tests and caffeine measurements, both individually and in combination, as predictors of the relative contribution of domestic waste to wastewater. Trace concentrations of caffeine in water and sediment samples were measured using gas chromatography ion-trap tandem mass spectrometry. In a series of step-wise multiple regression analyses, caffeine was found to be a useful and significant factor that helped to predict the extent of domestic land use and domestic waste concentrations in the environmental samples (p<0.05) , and in the laboratory study examining conditions in various blends of domestic and agricultural waste (p < 0.05). In a multiple analysis of covariance, caffeine levels showed a significant correlation with seasonally varying water parameters (p < 0.05). The use of caffeine as a contributing indicator of the relative contribution of domestic wastes in waterways is supported by the present study.
Keywords: Nutrient loading; Stormwater drainage; Domestic waste processing; Combined sewer overflow; Septic system leakage; Aquatic health; Microbiology